Comparative Costs of Growing Citrus in Florida and Sao Paulo (Brazil) for the 2000-01 Season - Ronald P. Muraro; Thomas H. Spreen; Marcos Pozzan (EDIS, 2003)
The states of Florida and Sao Paulo (Brazil) combined account for approximately 85 percent of the world's production of orange juice. Sao Paulo produces 45 percent of the total world production of orange juice and Florida produces about 40 percent. A 2000-01 comparison of the orange industry inFlorida and Sao Paulo is shown in Table 1 of this fact sheet. This is EDIS document FE364, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2003.